Análisis factorial de las características socioeconómicas del ganadero de las cuencas lecheras de la región Amazonas, 2009. - Torres-Armas y Cols., Elías Alberto (2019)
The objective of the present study was the characterization and identification of tipology of farmers producing milk in dairy watershed of the Amazonas region, with the purpose of that information can be used for the generation of differential actions of work. The methodology applied in the present study was descriptive, and the research method was the social survey. The unit of study was composed by three dairy watershed, the surveyed population was 74 farmers, distributed by proportional allocation in three dairy watershed: Pomacochas, Leymebamba and Molinopampa. The survey collected information related to technological and productive features of dairy production, also some social information was collected. The analysis of the information collected was divided in two stages: for the characterization descriptive statistics were used: means and deviations of the means. For the identification of the tipology, a Factorial Analysis of Multiple Correspondences was used. The description of the dairy producers in dairy watershed of the Amazonas region, confirmed the heterogeneity of technological, productive and social features that coexist among the farmers. The Factorial Analysis of Multiple Correspondences, allowed to distinguish three types of farmers, clearly differentiated by the composition of their variables.